Relationship between percentage of regulatory T-cells and dental amalgam fillings. - Fahad Khaliq; Nadeem Afzal; Muhammad Kashif; Faheem Shahzad (Universidad de Concepción., 2016)
Introduction: Regulatory T-cells are the main component of peripheral tolerance and their level is decreased in autoimmunity. In dental amalgam, a mixture of metals is used as a restorative material. During daily a ctivities, these metals are ingested and affect renal, neurosensory and immune systems. Studies have demonstrated an increased risk of autoimmune diseases in patients with dental amalgam fillings. It was hypothesized that the percentage of regulatory T-cells decreases in individuals with amalgam fillings. Therefore this study was designed to determine and compare the percentage of regulatory T-cells in individuals with and without amalgam fillings. Material and Methods: This was a cross-sectional study. Subjects were divided into two groups with each group consisting of 40 individuals. Group I (study group) comprised individuals with amalgam fillings, and Group II (control group), individuals without amalgam fillings in their teeth. Blood samples of all the participants were collected and tagged with CD4‑FITC, CD25‑PE and CD127‑PerCP-Cy monoclonal antibodies for the detection of regulatory T-cells, FACSCalibur was used for this purpose. Results: The percentage of regulatory T-cells in the control group was high (77.77±5.54%) compared to the study group (76.09±7.68%), however, on comparison, the difference was not statistically significant (p=0.25). Conclusion: Dental amalgam fillings did not show a declining effect on the percentage of regulatory T-cells.